A population profile of measles susceptibility in Tianjin, China. Issue 27 (8th June 2016) - Boulton, Matthew L.; Wang, Xiexiu; Zhang, Ying; Montgomery, JoLynn P.; Wagner, Abram L.; Carlson, Bradley F.; Ding, Yaxing; Li, Xiaoyan; Gillespie, Brenda; Su, Xu
Abstract: Background: Measles is a highly infectious illness requiring herd immunity of 95% to interrupt transmission. Measles is targeted for elimination in China, which has not reached elimination goals despite high vaccination coverage. We developed a population profile of measles immunity among residents aged 0–49 years in Tianjin, China. Methods: Participants were either from community population registers or community immunization records. Measles IgG antibody status was assessed using dried blood spots. We examined the association between measles IgG antibody status and independent variables including urbanicity, sex, vaccination, measles history, and age. Results: 2818 people were enrolled. The proportion measles IgG negative increased from 50.7% for infants aged 1 month to 98.3% for those aged 7 months. After 8 months, the age of vaccination eligibility, the proportion of infants and children measles IgG negative decreased. Overall, 7.8% of participants 9 months of age or older lacked measles immunity including over 10% of those 20–39 years. Age and vaccination status were significantly associated with measles IgG status in the multivariable model. The odds of positive IgG status were 0.337 times as high for unvaccinated compared to vaccinated (95% CI: 0.217, 0.524). Conclusions: The proportion of persons in Tianjin, China immune to measles was lower than herd immunity threshold with less than 90% of people aged 20–39 years demonstrating protection. Immunization programs in Tianjin have been successful in vaccinating younger age groups although high immunization coverage in infants and children alone would not provide protective herd immunity, given the large proportion of non-immune adults.